Kajian uji gelar aspal modifikasi berbasis karet padat jenis crepe rubber pada skala pilot - Bahruddin Bahruddin; Arya Wiranata; Eri Malindo; Alfian Malik; Robby Kumar (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The COVID-19 pandemic that hit Indonesia had a significant impact on the industrial sector. One of them is the natural rubber industry which has experienced a decline due to export restrictions from natural rubber export destination countries. This has a direct impact on rubber farmers who suffer financial losses. The formation of a new natural rubber downstream industry for natural rubber modified asphalt is a solution to increase national rubber consumption without relying on exports. Therefore, the purpose of carrying out the asphalt title test based on natural rubber type crepe rubber is to evaluate technical feasibility and educate the public about using natural rubber for domestic needs. This service method consists of several stages: observing the absorption potential of natural rubber, analyzing technical feasibility, and evaluating the degree test of natural rubber modified asphalt. The degree test was carried out on the 10-meter road around the Faculty of Engineering, Riau University. The results of the degree test show that the modified asphalt raw material is based on crepe rubber, the asphalt sample marshall test that was held, and the core drill test meets the 2018 Highways standard. The degree test that has been carried out can educate the community and rubber farmers through APKARKUSI regarding natural rubber processing technology and compound making. Crepe rubber and the technology of making modified asphalt and applying modified asphalt for roads.